LOFAR 144-MHz follow-up observations of GW170817. Issue 4 (14th April 2020) - Broderick, J W; Shimwell, T W; Gourdji, K; Rowlinson, A; Nissanke, S; Hotokezaka, K; Jonker, P G; Tasse, C; Hardcastle, M J; Oonk, J B R; Fender, R P; Wijers, R A M J; et al.
ABSTRACT: We present low-radio-frequency follow-up observations of AT 2017gfo, the electromagnetic counterpart of GW170817, which was the first binary neutron star merger to be detected by Advanced LIGO–Virgo. These data, with a central frequency of 144 MHz, were obtained with LOFAR, the Low-Frequency Array. The maximum elevation of the target is just 13${_{.}^{°}}$ 7 when observed with LOFAR, making our observations particularly challenging to calibrate and significantly limiting the achievable sensitivity. On time-scales of 130–138 and 371–374 d after the merger event, we obtain 3σ upper limits for the afterglow component of 6.6 and 19.5 mJy beam −1, respectively. Using our best upper limit and previously published, contemporaneous higher frequency radio data, we place a limit on any potential steepening of the radio spectrum between 610 and 144 MHz: the two-point spectral index $α ^{610}_{144} \gtrsim$ −2.5. We also show that LOFAR can detect the afterglows of future binary neutron star merger events occurring at more favourable elevations.